50 Differences That Make a Difference: A Compendium of Frequently Confused Term Pairs in Psychology - Lilienfeld, Scott O.; Pydych, Ava L.; Lynn, Steven Jay; Latzman, Robert D.; Waldman, Irwin D. (Frontiers in Education, 2017)
An adequate understanding of specialized terminology is a prerequisite for the mastery of core concepts across all scientific disciplines, including psychological science. In a previous article in this journal (Lilienfeld, Sauvigne, Lynn, Cautin, Latzman, & Waldman, 2015), we presented an annotated list of 50 widely used psychological terms that should generally be avoided, or at best used judiciously and with qualifications in select cases. Herein, we offer a “sequel” by presenting a list of 50 term pairs in psychology and allied fields (e.g., psychiatry, cultural anthropology, statistics) that are commonly confused in academic writing, popular writing, or both. We draw these terms from multiple domains of psychology, including Sensation, Perception, Learning, and Memory; Social and Cultural Bases of Behavior; Personality Psychology; Psychopathology; and Research Methodology and Statistics. Many of these terms are frequently confused not merely by beginning psychology students, but also by advanced psychology students, psychology instructors, and science journalists. Our list of commonly confused psychological term pairs should hopefully be a modest contribution toward enhancing psychological literacy as well as critical thinking in psychology more broadly.